Open Water Swimming: Swimmers’ Kinematical and Neuromuscular Characterisation in 5 km Swim - Conceiço, Ana; Marinho, Daniel; Šťastný, Jan; Gonçalves, Carlos; Freitas, Joo; da Costa-Machado, Renato; Louro, Hugo (MDPI, 2025)
This study aimed to characterize and analyse the kinematic parameters and muscle activity of swimmers in open water swimming (OWS). Nine male swimmers (age: 25.4 +/- 11.9 years; body mass: 75.9 +/- 9.0 kg; height: 180.7 +/- 6.7 cm; and arm span: 185.6 +/- 10.3 cm) were evaluated in an open environment (lake), performing 5 m x 1000 m at maximum intensity, with a rest of 30 s every 1000 m. For kinematical analyses, the stroke rate (SR), swimming velocity (v), stroke length (SL), and stroke index (SI) were calculated. Surface EMG data were recorded in seven muscles-upper trapezius (UP); latissimus dorsi (LD); pectoralis major (PM); posterior deltoid (PD); anterior deltoid (AD); triceps brachii (TB); and biceps brachii (BB)-for the underwater and recovery phases of the stroke. SL (F = 3.41, p = 0.06, eta 2 = 0.30) and SI (F = 3.29, p = 0.08, eta 2 = 0.29) changed along the covered distances, and SR (F = 1.54, p = 0.24, eta 2 = 0.16) increased, especially in the last 1000 m (32.5 +/- 3.0 cycles-min-1). AD was highly activated in recovery, showing statistical differences from the beginning (p
Keywords: biomechanics; open water swimming; surface electromyography; freestyle